2021
DOI: 10.1080/01902148.2021.1881189
|View full text |Cite
|
Sign up to set email alerts
|

PDE3-inhibitor enoximone prevented mechanical ventilation in patients with SARS-CoV-2 pneumonia

Abstract: Background: Standard care in severe SARS-CoV-2 pneumonia complicated by severe dyspnea and respiratory failure, consists of symptom reduction, ultimately supported by mechanical ventilation. Patients with severe SARS-CoV-2, a prominent feature of COVID-19, show several similar symptoms to Critical Asthma Syndrome (CAS) patients, such as pulmonary edema, mucus plugging of distal airways, decreased tissue oxygenation, (emergent) exhaustion due to severe dyspnea and respiratory failure. Prior application of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…(3) Beute et al reported four cases of severe respiratory insufficiency related to SARS-CoV-2 pneumonia in which the endovenous administration of enoximone prevented mechanical ventilation. (4) In our case we administered aerosolized enoximone basing on the pharmacodynamic idea that inhaled administration of PDE inhibitors applies the drug directly to the site of action minimizing systemic exposure and increasing the therapeutic index. In particular, the need to restore vasodilation in aerated lungs makes inhaled route as the potential perfect way of drug administration in COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Beute et al reported four cases of severe respiratory insufficiency related to SARS-CoV-2 pneumonia in which the endovenous administration of enoximone prevented mechanical ventilation. (4) In our case we administered aerosolized enoximone basing on the pharmacodynamic idea that inhaled administration of PDE inhibitors applies the drug directly to the site of action minimizing systemic exposure and increasing the therapeutic index. In particular, the need to restore vasodilation in aerated lungs makes inhaled route as the potential perfect way of drug administration in COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the above, colchicine (see above) attenuates the inflammatory response by interfering with pathways that include the TNFα-induced nuclear factor κΒ (NF-κΒ) pathway [ 39 ]. The PDE3-inhibitors, milrinone and enoximone, are reported to help treat respiratory failure in patients with severe SARS-CoV-2 pneumonia [ 40 ]. PDE3-inhibitors prevent microvascular leakage (via a normalization of the cytoskeleton by increasing intracellular cAMP) and increase the ciliary beat frequency of the epithelial cells within the respiratory tract ([ 40 ] and references therein); moreover, the anti-inflammatory properties of PDE3-inhibitors may help prevent the cytokine storm [ 41 ].…”
Section: Therapeutic Approaches To Covid-19 Based On the Cytoskeletonmentioning
confidence: 99%
“…The PDE3-inhibitors, milrinone and enoximone, are reported to help treat respiratory failure in patients with severe SARS-CoV-2 pneumonia [ 40 ]. PDE3-inhibitors prevent microvascular leakage (via a normalization of the cytoskeleton by increasing intracellular cAMP) and increase the ciliary beat frequency of the epithelial cells within the respiratory tract ([ 40 ] and references therein); moreover, the anti-inflammatory properties of PDE3-inhibitors may help prevent the cytokine storm [ 41 ]. Finally, dexamethasone has been shown to preserve the intestinal mucosal barrier and to shorten the length of hospitalization of COVID-19 patients [ 42 ].…”
Section: Therapeutic Approaches To Covid-19 Based On the Cytoskeletonmentioning
confidence: 99%
“…
Ferro et al describe a patient with severe respiratory insufficiency caused by SARS-CoV-2 infection, who improved greatly (without tracheal intubation) by administration of nebulized phosphodiesterase-3-(PDE3-) inhibitor enoximone.Using enoximone as a treatment for respiratory insufficiency due to SARS-CoV-2 infection was earlier described by Beute et al (1) and suggested by Giorgi et al (2) Beute et al describe systemic delivery of PDE3, whereas Ferro used a nebulized administration form.Both are limited cases, but significant for the treatment of SARS-CoV-2-induced respiratory insufficiency, especially when linked to evidence of the efficiency of enoximone in asthma and status asthmaticus. A potent vasodilator, enoximone proved to be an equally potent bronchodilator, extremely suitable in respiratory diseases, even in low doses.
…”
mentioning
confidence: 99%
“…A potent vasodilator, enoximone proved to be an equally potent bronchodilator, extremely suitable in respiratory diseases, even in low doses. (1,3,4) Ferro et al used nebulized administration, choosing to minimize systemic exposure.…”
mentioning
confidence: 99%